Peran Pemerintah Dalam Menginventarisasi Ekspresi Budaya Tradisional Indonesia - Herzani, Andhika Putra (UI Scholars Hub, 2020)
The development of an increasingly advanced era, the expression of traditional culture (EBT) is vulnerable to exploitation by other parties due to the lack of awareness of the importance of the assets of intellectual works and is not well documented or documented EBT. Inventory is one of the Defensive Protection steps, a step taken by building an accurate database and inventory, registration or recording that must be played by the State. Preventive protection needs to be recorded or an inventory of Indonesias traditional culture to prevent cases of cultural claim by other countries which would certainly harm the Indonesian nation and be used by those who have experienced cases of EBT abuse as a basis for proof. Inventory should ideally be carried out by an institution that is implicitly a State representative institution, in supporting the inventory it should also optimize the Ministry of Education and Culture and coordinate with DJKI in taking comprehensive inventory or documentation actions